Legal Reconstruction of Indonesian Banking Laws: Challenges and Opportunities for Digital Bank Regulation - Wardah Yuspin; Anindhita Nurfaatin Sukirman; Arief Budiono; Jompon Pitaksantayothin; Ata Fauzie (Varia Justicia, 2023)
Digital banks in Indonesia are growing rapidly. This phenomenon has given rise to legal disharmony in laws and regulations, considering that banks are institutions with many regulations (fully regulated). Legal disharmony occurs because of the many weaknesses in the current banking regulations, which still focus on the Banking Laws. Law Number 10 of 1998 concerning banking was formed specifically to regulate conventional banking transactions, while the concept of digital banks in its implementation utilizes technology. This difference creates a gap leading to a legal vacuum. By interpreting the articles of Law Number 10 of 1998 concerning banking using a textual approach (focusing on text), this study unveiled that, as the basis for regulating digital banks, this law was still extremely low, limited and no longer compatible with the development of digital banks. Therefore, it is necessary to establish regulations for digital banks to provide legal protection to realize the legal goal of creating justice and legal certainty for the current and future development of the digital banking industry.